A Machine Learning Based Fake News Content Detection Using NLP - Pranav Ashtaputre, Ashutosh Nawale, Rohit Pandit (International Journal of Advanced Science and Technology, 2020)
Fake news is a current trend going on with the emergence of technology. It has the potential to hurt people, cause riots and even poses a danger to democracy. It provides an opportunity for agitators to spread forged news or false propaganda causing unrest in the public. Since then, detecting fake news has become a critical issue and every organization is trying to establish a method to detect and counter fake news. We propose in this, a fake news detection model that uses NLP with machine learning techniques. We compare different classifier models and different extraction techniques to find out which model gives the best results.